Bimbingan Keagamaan dengan Teknik Reward dan Punishment untuk Meningkatkan Kedisiplinan Belajar Siswa - Azmiah, Adilah; Arifin, Isep Zaenal; Tajiri, Hajir (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This study aims to determine the condition of the learning discipline of class VI students at Madrasah Ibtidaiyah Plus Annur. To find out the program and application of religious guidance through reward and punishment techniques that have been implemented in schools. As well as knowing the results to be achieved with this reward and punishment technique. The method used in this research is a qualitative approach. The results of the study show that first, the initial conditions for student discipline in class VI are said to be not disciplined. Second, the religious guidance program with reward and punishment techniques makes students more active in their learning. Third, the implementation of a religious guidance program with reward and punishment techniques becomes a means of controlling student education while studying. Fourth, the results obtained with the reward and punishment technique of students are more disciplined in participating in learning.